PENGARUH PARTISIPASI PENGANGGARAN, PENEKANAN ANGGARAN, KOMITMEN ORGANISASI, ASIMETRI INFORMASI, DAN KETIDAKPASTIAN LINGKUNGAN TERHADAP BUDGETARY SLACK PADA HOTEL-HOTEL BERBINTANG DI KOTA DENPASAR - SUJANA, I KETUT (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 5 No 2 (2010))
Business participants are expected to run their business effectively and efficiently in a competitive business environment. To cope with this situation, planning and controlling are the keys to success in which budgeting is an important element requiring full participation. This participation may provide an authority to managers to prepare a budget for each responsibility center that they belong to. In many cases, this authority would probably lead to budgetary slack where participants earn benefits from the budget as a performance evaluation tool at the expense of others and the organization as a whole. This budgetary slack might be as a result of asymmetric information between top management and the lower one. This research aims to investigate the effect of budget participation, budget pressure, organization commitment, asymmetric information, and uncertainty of business circumstances on budgetary slack in star hotels in Denpasar. To deal with this research purpose, purposive sampling method is used with 11 hotels and 43 participants. In addition, multiple linear regression is run as an analytical technique to answer the research questions. The reseach concludes that budget participation, budget pressure, organization commitment and uncertainty of business circumstances do not have significant effect on budgetary slack in star hotels in Denpasar. The only variable that has significant effect is asymmetric information.
Keywords: budget participation, budget pressure, organization commitment, uncertainty of business circumstances, budgetary slack